Pengaruh Subtitusi Tepung Umbi Garut (Marantha Arundinaceae) terhadap Mutu Organoleptik Donat Kentang - Firdausy, Putri Ayu; Ita Fatkhur Romadhoni; Niken Purwidiani; Mauren Gita Miranti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research was conducted using local food ingredients, namely arrowroot flour substituted in potato donuts. The objectives of this study were to determine: 1) the best formula for substituting arrowroot flour in potato donuts; 2) determine the organoleptic quality characteristics of arrowroot flour substitution in potato donuts; 3) determine the best selling price of potato donut substitution. Using an experimental method with three different formulations, the ratio of wheat flour and arrowroot flour included 55%:45%, 70%:30%, and 85%:15%. Organoleptic tests were conducted by 30 panelists, consisting of 25 semi-trained panelists and 5 trained panelists, who assessed the parameters of shape, color, aroma, texture, taste, and level of preference. The test data were analyzed using a single ANOVA test and continued with a Duncan test to determine the differences between treatments. The analysis results show that: 1) the best formula 85%:15% has a value of 18.82 with the criteria of a fairly round symmetrical shape, light brown in color, quite potato-flavored, quite soft in texture, and tastes quite savory and slightly sweet; 2) produces potato donut criteria that are quite round symmetrical, brown in color, potato-flavored, soft in texture, and tastes savory and slightly sweet; 3) the selling price of the best formula is set at Rp.5600 per unit with a weight of 40 grams.